Вклад доктора біологичних наук, професора Л.І. Рубцова в проектування та будівництво парків України - Rubtsova, O.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The contribution of Doctor of Biological Sciences, Professor L.I. Rubtsov to the planning of the five Ukrainian parks is studied: Askania-Nova (Kherson Region) Aleksandrovskiy Landscape Park (Dnipropetrovsk Region), Dievo-Taromsk recreation area (Dnipropetrovsk Region), garden and park area on Khortytsya isle (Zaporizhzhia Region), park of the 50th anniversary of the Great October Revolution (nowadays – the “Pine Forest”) in Cherkassy. All these works were performed under the direction of L.I. Rubtsov, as the main consultant of the projects in the workshops of institutes “Giprograd” and “UkrNIIinzhproekt”. Historical, functional, aesthetic and ecological approach to planing solutions is analyzed. The importance of the creation of parks in the steppe regions is emphasized. The neсessity of the study of the creative heritage L.I. Rubtsov – a prominent landscape architect – for the history of landscape art of Ukraine is accentuated.